Truncated Patch Antenna with two different substrate materials for GPS application - Mokhlis, Nur Abilla; Al-Fadhali, Najib; Majid, Huda; Salih Mohammed , Mohammed; A. A. Mukred, Jameel; Alduais, Nayef; Aship, Adel; Abo Mosali, Najmaddin (Journal of Advanced Industrial Technology and Application, 2022)
In the wireless communication technology, the microstrip patch antenna has gained an intensive application due to their light weight, small size, easy reproduction, and integration ability with circuitry. Therefore, this research presents the work in designing planar microstrip patch antenna for GPS using microstrip line feed that can operate at 1.575 GHz with corresponding polarization. Furthermore, analysis done on a two different substrate that is Taconic TLC-32 and FR-4 with dielectric constant 3.2 and 4.3 respectively. Comparison is done among these two different substrates which use microstrip feed line, feeding insect and truncated two opposite edged of the squared patch. The performance of the patch antenna is demonstrated by the simulated bandwidth, return loss, gain and radiation pattern. From the study, shows that the antenna that used RF-4 substrate has a better performance and have a smaller size compared to Taconic TLC-32. The results show that simulated and measured resonate frequency for return loss is -14.60 and -14.15 dB at 1.575 GHz. It is also by implementing the feeding insect technique, it could improve the performance of antenna. Both simulated and experimental result shows that the prototype has good performance, and it is suitable for GPS application